Tributación de los activos biológicos: gastos deducibles o capitalización en el activo - Jiménez Zeledón, Mariano (2026)
This essay reviews the concept of biological assets in accordance with IAS 41, the adoption of international financial standards by the Costa Rican legal system and their interpretation by the Tax Administration. In addition, the tax regulations related to biological assets and their application to specific cases are analyzed through administrative and judicial jurisprudence.